Nová stříbrná kaptorga ze středních Čech v souvislosti s konkrétním výrobním okruhem(?) v Praze - Naďa Profantová; David Daněček (Slavia Antiqua, 2018)
In response to the new find of a small silver trapezoid casket — i.e. kaptorga — from the grave of female H 2103 from Hostivice-Palouky, we focused our paper on the small group of such amulet caskets from Central Bohemia, decorated with engraved animal motifs on a punched background and with a knot made with the assistance of a pair of compasses on their lids and dated to the 2nd half of the 10th century. The kaptorga from Hostivice belongs to the Bohemian openable construction type IA, and was decorated with an engraving of a pair of birds with their heads turned on eitherr side of a stylized tree of life with leaf-shaped tendrils. Most of the finds from Hostivice, Klecany II, Praha-Lumbe Garden were produced in Prague during the 2nd half of the 10th century.